The efficacy of three-dimensional Schroth exercises in adolescent idiopathic scoliosis: a randomised controlled clinical trial - KURU ÇOLAK, TUĞBA (SAGE PUBLICATIONS LTD, 2016)
Objective: To compare the efficacy of three-dimensional (3D) Schroth exercises in patients with adolescent idiopathic scoliosis. Design: A randomised-controlled study. Setting: An outpatient exercise-unit and in a home setting. Subjects: Fifty-one patients with adolescent idiopathic scoliosis. Interventions: Forty-five patients with adolescent idiopathic scoliosis meeting the inclusion criteria were divided into three groups. Schroth's 3D exercises were applied to the first group in the clinic and were given as a home program for the second group; the third group was the control. Main Measures: Scoliosis angle (Cobb method), angle of rotation (scoliometer), waist asymmetry (waist - elbow distance), maximum hump height of the patients and quality of life (QoL) (SRS-23) were assessed pre-treatment and, at the 6(th), 12(th) and 24(th) weeks. Results: The Cobb (-2.53 degrees; P=0.003) and rotation angles (-4.23 degrees; P=0.000) significantly decreased, which indicated an improvement in the clinic exercise group compared to the other groups. The gibbosity (-68.66mm; P=0.000) and waist asymmetry improved only in the clinic exercise group, whereas the results of the other groups worsened. QoL did not change significantly in either group. Conclusion: According to the results of this study the Schroth exercise program applied in the clinic under physiotherapist supervision was superior to the home exercise and control groups; additionally, we observed that scoliosis progressed in the control group, which received no treatment.
Keywords: Adolescent idiopathic scoliosis; exercise; Schroth method; PUBERTAL CHANGES; RELIABILITY; VALIDITY; PATTERN